Research progress about the effect and prevention of blue light on eyes - Zhao, Zhi-Chun (Int J Ophthalmol, 2018)
In recent years, people have become increasingly attentive to light pollution influences on their eyes. In the visible spectrum, short-wave blue light with wavelength between 415 nm and 455 nm is closely related to eye light damage. This high energy blue light passes through the cornea and lens to the retina causing diseases such as dry eye, cataract, age-related macular degeneration, even stimulating the brain, inhibiting melatonin secretion, and enhancing adrenocortical hormone production, which will destroy the hormonal balance and directly affect sleep quality. Therefore, the effect of Blu-rays on ocular is becoming an important concern for the future. We describe blue light's effects on eye tissues, summarize the research on eye injury and its physical prevention and medical treatment.